If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6)(x + 6) = (x + -6)(x + -6) Reorder the terms: (-6 + x)(x + 6) = (x + -6)(x + -6) Reorder the terms: (-6 + x)(6 + x) = (x + -6)(x + -6) Multiply (-6 + x) * (6 + x) (-6(6 + x) + x(6 + x)) = (x + -6)(x + -6) ((6 * -6 + x * -6) + x(6 + x)) = (x + -6)(x + -6) ((-36 + -6x) + x(6 + x)) = (x + -6)(x + -6) (-36 + -6x + (6 * x + x * x)) = (x + -6)(x + -6) (-36 + -6x + (6x + x2)) = (x + -6)(x + -6) Combine like terms: -6x + 6x = 0 (-36 + 0 + x2) = (x + -6)(x + -6) (-36 + x2) = (x + -6)(x + -6) Reorder the terms: -36 + x2 = (-6 + x)(x + -6) Reorder the terms: -36 + x2 = (-6 + x)(-6 + x) Multiply (-6 + x) * (-6 + x) -36 + x2 = (-6(-6 + x) + x(-6 + x)) -36 + x2 = ((-6 * -6 + x * -6) + x(-6 + x)) -36 + x2 = ((36 + -6x) + x(-6 + x)) -36 + x2 = (36 + -6x + (-6 * x + x * x)) -36 + x2 = (36 + -6x + (-6x + x2)) Combine like terms: -6x + -6x = -12x -36 + x2 = (36 + -12x + x2) Add '-1x2' to each side of the equation. -36 + x2 + -1x2 = 36 + -12x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -36 + 0 = 36 + -12x + x2 + -1x2 -36 = 36 + -12x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -36 = 36 + -12x + 0 -36 = 36 + -12x Solving -36 = 36 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -36 + 12x = 36 + -12x + 12x Combine like terms: -12x + 12x = 0 -36 + 12x = 36 + 0 -36 + 12x = 36 Add '36' to each side of the equation. -36 + 36 + 12x = 36 + 36 Combine like terms: -36 + 36 = 0 0 + 12x = 36 + 36 12x = 36 + 36 Combine like terms: 36 + 36 = 72 12x = 72 Divide each side by '12'. x = 6 Simplifying x = 6
| (x-6)(x+6)=(x-6)x(x-6) | | y-5.9=7.22 | | 8x+18=30 | | 2x^4y^2z^2= | | 0=9x+0.25y | | 3Xsquare-13X-10=0 | | 3y^2-11y-30=0 | | 4+25=100 | | 2(3z+3)=(2+1)(3-5) | | 5f+20-6f-30= | | X-3y=36 | | 20=12((5-x)+x+(4-x))+10-((5-x)+x+(6-x))+11-((4-x)+x+(6-x)) | | 20=(12((5-x)+x+(4-x)))+(10-((5-x)+x+(6-x)))+(11-((4-x)+x+(6-x))) | | 9x-5x-8=360 | | 7x-13-x=5 | | x=5x-25 | | 9x-5x-8= | | 5x+25=7x+50 | | -20z+28=25-16z-12+2z-6z | | y=x^2+m-4x | | 3*2+2=7*2-6 | | 2p+3-3p+8= | | a^2-6a+6=0 | | a^2-8a+b^2-2b+17=0 | | 9a^2-6a+b^2-2b+2=0 | | 35=-10+2x | | 3.7x=0.4 | | (12x^2)+(5x^2)+4x= | | 51+14x=x | | 4*(2x+3)-x*(4-x)=x*(x+1)+3*(x+4) | | 4xsquared-13x+9=-5x+6 | | 9-3k=0 |